Integrasi Media Pembelajaran Wordwall dalam Model Pembelajaran Studi Kasus (CBL) pada Pembelajaran IPA Di Sekolah Dasar untuk Meningkatkan Hasil Belajar - Sarah Masyitha Elysia; Idam Ragil Widianto Atmojo (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
The use of interactive learning materials in elementary school education is driven by technological advances in this digital era. One of these effective learning media in improving students' learning outcomes and critical thinking skills is by using Wordwall. The purpose of this study is to investigate how well Wordwall in the case study learning model (CBL) in science subjects in elementary school environments integrates learning media. This researcher's approach consists of examining the literature on five related scientific publications that have been indexed by SINTA between 2020 and 2025. The results of this study state that using Wordwall can significantly increase students' interest, motivation and learning outcomes. In addition, there is a media that supports teachers in terms of delivering material in a fun and creative way. The conclusion of this study shows how Wordwall is useful as a tool to improve student learning outcomes in science classes in elementary schools.